Incentivizing COVID-19 vaccination among racial/ethnic minority adults in the United States: 209 per dose could convince the hesitant - Kevin Chen; Marta Wilson-Barthes; Jeffrey E. Harris; Omar Galarraga (Health Economics Review, 2023)
Background: More than two years into the coronavirus disease (COVID-19) pandemic, it remains unclear whether fnancial incentives can reduce vaccine hesitancy and improve uptake among key unvaccinated populations. This study estimated the willingness of racial/ethnic minority adults in the United States to accept fnancial incentives for COVID-19 vaccination and the minimum amount needed to vaccinate a sufciently high percentage of this population. Methods: From August through September 2021, we conducted an online survey of 367 Black/African American and Hispanic patients, age=18 years, from 8 community health centers in Rhode Island. Contingent valuation questions assessed respondents' willingness-to-accept (WTA) incentives for COVID-19 vaccination using random-startingpoints and iterative incentive ofers of 5 to 50 per dose. Ordered logistic regression models examined associations between respondent characteristics and WTA. Predictive probabilities were modeled using both within-survey range and out-of-survey range incentive ofer amounts and compared against vaccination thresholds needed to reach herd immunity. Results: Less than 30% of unvaccinated survey respondents were WTA an incentive of 50/dose for vaccination. Mod- els using out-of-survey incentive ofer amounts greater than 50 suggested that 85% of respondents would agree 140/dose (95% CI: 43-236) could convince other people to accept vaccination, while 209/dose (95% CI: -91509) would be needed for 85% of respondents to accept vaccination themselves. Conclusions: Findings from this analysis may inform the design of incentive schemes aiming to reduce racial/ethnic disparities in vaccine and booster uptake, which will continue to be important as new variants of SARS-CoV-2 emerge.
Keywords: 330; Financial incentives; Vaccination; COVID-19; Contingent valuation; Willingness-to-accept; United States